Qualitative study of the feasibility and acceptability of implementation, and potential mechanisms of Learning Together for Mental Health, a whole-school intervention aiming to promote mental health and wellbeing in secondary schools - Neisha Sundaram; Oliver Lloyd-Houldey; Semina Michalopoulou; Steven Hope; Joanna Sturgess; Elizabeth Allen; Rosa Legood; Stephen Scott; Lee D. Hudson; Dasha Nicholls; Deborah Christie; Russell M. Viner; et al. (Pilot and Feasibility Studies)
Abstract Background Despite high rates of adolescent mental-health problems, there are few effective whole-school interventions to address this. Whole-school interventions offer a feasible and sustainable means of promoting mental health. We previously evaluated the Learning Together (LT) intervention which was effective in preventing bullying (primary outcome), promoting mental well-being, psychological functioning, and reducing substance use (secondary outcomes). We adapted LT to develop Learning Together for Mental Health (LTMH) with a new menu of evidence-based actions to address mental health and an enhanced SEL curriculum. Methods We undertook a feasibility study of LTMH, a whole-school intervention featuring needs assessment, student and staff participation in decision-making via action groups selecting actions from an evidence-based menu, restorative practice, and a SEL and resilience skills curriculum between 2022 and 2023. This article examines the feasibility, acceptability, and potential mechanisms of LTMH, qualitatively, drawing on interviews and focus groups with 49 students in years 8 and 10, and 20 staff across four state secondary schools in southern England. Results The intervention was feasible and acceptable to implement. In terms of feasibility, the SEL curriculum was the most challenging to implement and was not prioritised by schools that had existing social and emotional learning lessons. Training and external facilitation were well-rated. Some schools struggled with the resourcing and workload implications of implementing actions from the evidence-based menu. Some aspects were not clear. Some staff were not aware that the various components worked together. Needs reports were not easy to understand for all. Students were generally supportive of restorative practice and SEL lessons. Data supported a potential mechanism involving increased school belonging and developing practical knowledge and skills to manage emotions and relationships. The intervention has little potential for harm. Conclusions The intervention is ready for phase III trial with minor adaptations. A phase III trial of effectiveness is justified. Trial registration ISRCTN15301591 https://doi.org/10.1186/ISRCTN15301591